2016
DOI: 10.1007/s11739-016-1517-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation in patients with atrial fibrillation and medical non-neoplastic disease in a terminal stage

Abstract: Many patients with non-neoplastic disease develop atrial fibrillation in advanced stages of their disease. The aim of this study is to determine the factors associated with the use of oral anticoagulants in patients with atrial fibrillation and non-neoplastic medical disease in a terminal stage, and whether their use is associated with a longer survival. Design is prospective, observational, multicentre study. Patients with atrial fibrillation and non-neoplastic disease (severe not reversible organ insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…So, we investigated the role of a wide range of prescribed drugs for developing delirium. Anticoagulants (warfarin, heparin, enoxaparin) reduced the chances of developing delirium, similar to a previous study by Diez-Manglano et al [ 41 ] which found anticoagulants to be associated with lower delirium prevalence in patients with atrial fibrillation. Nevertheless, Lahariya et al [ 42 ] reported an increase in delirium risk by receiving warfarin in patients admitted to a cardiac intensive care unit, while Ranhoff et al [ 43 ] found no relation between warfarin use and the risk of delirium.…”
Section: Discussionsupporting
confidence: 87%
“…So, we investigated the role of a wide range of prescribed drugs for developing delirium. Anticoagulants (warfarin, heparin, enoxaparin) reduced the chances of developing delirium, similar to a previous study by Diez-Manglano et al [ 41 ] which found anticoagulants to be associated with lower delirium prevalence in patients with atrial fibrillation. Nevertheless, Lahariya et al [ 42 ] reported an increase in delirium risk by receiving warfarin in patients admitted to a cardiac intensive care unit, while Ranhoff et al [ 43 ] found no relation between warfarin use and the risk of delirium.…”
Section: Discussionsupporting
confidence: 87%
“…The strength of the lower limbs measured by the sit and stand up test is a biomarker of disease severity [ 61 ] that is partly due to malnutrition and a lack of exercise [ 62 ]. These factors contribute to ageing adverse events, such as falls, which can produce head trauma that increases mortality in older patients with anticoagulant pharmacy [ 63 ], a known risk for older people [ 64 ]. Readmission before 30 days of discharge should be considered as another frailty indicator, but has not often been recognized as such.…”
Section: Discussionmentioning
confidence: 99%
“…However, a poorer cognitive state was associated with not starting OA therapy. In fact, the ability to carry out basic activities of daily living has been a determinant of survival in polypathological patients or those with advanced disease with NVAF …”
Section: Discussionmentioning
confidence: 99%
“…In fact, the ability to carry out basic activities of daily living has been a determinant of survival in polypathological patients or those with advanced disease with NVAF. 25,28 Within 18 months, 25-30% of the patients with NVAF discontinued OA therapy. 29 The discontinuation of OA for patients with NVAF has not improved with the new direct-acting OA, 30 and has been associated with younger age, anemia, bleeding, frailty, low life expectancy, hospitalizations and emergency department visits.…”
Section: Discussionmentioning
confidence: 99%